Evaluating PET–CT in routine surveillance and follow‐up after treatment for cervical cancer: a cost‐effectiveness analysis. (3rd December 2013) - Auguste, P; Barton, P; Meads, C; Davenport, C; Małysiak, S; Kowalska, M; Zapalska, A; Guest, P; Martin‐Hirsch, P; Borowiack, E; Khan, K; Sundar, S; et al.
<x xml:space="preserve">Abstract</x> Objective To undertake a cost‐effectiveness analysis that compares positron emission tomography – computed tomography (PET‐CT) imaging plus standard practice with standard practice alone in the diagnosis of recurrent or persistent cervical cancer during routine surveillance and follow‐up of women who have previously been diagnosed and treated. Design Model‐based economic evaluation using data from a systematic review, supplemented with data from other sources, and taking a UK National Health Service (NHS) perspective. Setting Secondary Care in England. Population Women at least 3 months after the completion of treatment, with either recurrent or persistent cervical cancer. Methods A state transition (Markov) model was developed using TreeAge Pro 2011. The structure of the model was informed by the reviews of the trials and clinical input. In the model, two diagnostic strategies were examined. A one‐way sensitivity analysis, probabilistic sensitivity analysis, and a value of information analysis were also carried out. Main outcome measures Cost‐effectiveness based on incremental cost per quality‐adjusted life year (QALY). Results Adding PET–CT to the current treatment strategy of clinical examination and scanning [magnetic resonance imaging (MRI) and/or CT scan] during the routine surveillance and follow‐up of women with recurrent or persistent cervical cancer is significantly more costly, with only a minimal increase in effectiveness. The incremental cost‐effectiveness ratio (ICER) for the strategy of PET–CT as an adjunct to the standard treatment strategy that included clinical examination, MRI, and/or CT scan, compared with the usual treatment alone, was over £1 million per QALY. Conclusion The results of the current analysis suggest that use of PET–CT in the diagnosis of recurrent or persistent cervical cancer is not cost‐effective. Current guidelines recommending imaging using PET–CT as a diagnostic or surveillance tool need to be reconsidered in light of these results. This study did not specifically investigate the use of PET–CT in women with symptoms and radiological suspicion of recurrence where exenteration was considered. More research in that specific area is required.